Determination on Yellow Fin Tuna Stock (Thunnus albacares) In South Java Sea Based on Genetic Variation by Restriction Fragment Length Polymorphism (RFLP) Method - Feni Iranawati; Lazimatun Nazifah; Ledhyane Ika Harlyan; Syarifah Hikmah Julinda Sari; Diana Arfiati (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Brawijaya, 2016)
Indonesia is known as a country with the highest potential production of tuna, with total production more than six hundred thousand ton per year as value as 6.3 trillion IDR per year.However, Tuna fishery have several challenges, as can be identify by the declining in productivity and an average length fish had been caught, and also tuna fishing groundsaregetting farther. This apparently appears as a result of inaccurate determination of fish stock as the basic management unit of tuna fisheries, especially in yellow fin tuna (YFT). This study aims to define population stocks of YFTin South Java Sea based on genetic information. Samples were taken from three fish landing ports (MuaraBaru, Cilacap and Benoa). Restriction Fragment Length Polymorphism (RFLP) technique were applied for Cytochrome Oxidase I genes, using restriction enzymes;HaeIII, RsaI, BamHI, XhoI, and AluI. Genetic variation in populations were evaluated with POPGENE32 software. Result indicate that finer scale of stocks present YFT and should bemanaged differently for effective management purpose and to maintain sustainability of this species.